Exploring the Impact of Fintech Innovation on Financial Stability and Regulation: A Qualitative Study - Wijayanti, Handayani Tri; Sriyanto, S. (Golden Ratio of Finance Management, 2025)
This qualitative study explores the multifaceted dynamics of fintech innovation, financial stability, and regulation. The research aims to investigate the impact of fintech innovations on financial stability, identify associated risks and challenges, and examine regulatory responses to mitigate these risks. Employing a comprehensive research methodology encompassing exploratory and descriptive approaches, the study synthesizes existing literature from academic journals, reports, and other scholarly sources. Data collection involves systematic searches of databases such as PubMed, Scopus, Web of Science, and Google Scholar, supplemented by citation chaining and hand-searching techniques. Data analysis entails iterative rounds of coding, categorization, thematic analysis, and interpretation to uncover patterns, themes, and insights embedded within the literature. The research findings highlight the significant potential of fintech innovation to enhance financial inclusion, efficiency, and transparency while also identifying risks related to cybersecurity threats, data privacy concerns, and systemic vulnerabilities. Regulatory responses, including regulatory sandboxes, licensing regimes, and innovation hubs, are examined as mechanisms to foster innovation while safeguarding financial stability and consumer protection. The study contributes to advancing our understanding of the complex interactions between fintech innovation, financial stability, and regulation, providing insights to policymakers, regulators, industry stakeholders, and researchers.